PENGARUH PENDIDIKAN TENTANG KESEHATAN SEKSUALITAS TERHADAP SIKAP REMAJA DI RT. 06/RW. 05 KELURAHAN TLOGOMAS, KECAMATAN LOWOKWARU MALANG - Marianus Dakosta; Sri Mudayati; Novita Dewi (Universitas Tribhuwana Tunggadewi, 2014)
In general, teens (adolescents) are defined as the persons who experience the transition from childhood to adulthood. Adolescents involved in sexual activity because variety of reasons, such as: to obtain a pleasant sensation, satisfy the sex drive, satisfy the curiosity, a sign of conquest, expression of affection, or they are not able to withstand the pressure to adapt. This is happened because basically the best sex education is provided by the parents themselves, and can also be realized with the way of life of parents in the family as a husband and wife that are united in marriage. The purpose of this study is to analyze the effect (the influence) of sexuality health education to adolescent (teens) attitudes before and after be given sexuality health education in RT.06 RW.05 Village of Tlogo Mas, District. Lowokwaru. The method of this study use a Quasi Experiment Design with One Group Pretest Posttest Design Model. The sampling is sampling the samples saturated with 23 people. Statistical analysis Spearman rho correlation with p value of 0.000